Will Universal Access to Antiretroviral Therapy Ever be Possible? The Health Care Worker Challenge - André R Maddison; Walter F Schlech (Canadian Journal of Infectious Diseases and Medical Microbiology)
The United Nations millennium development goal of providing universal access to antiretroviral therapy (ART) for patients living with HIV/AIDS by 2010 is unachievable. Currently, four million people are receiving ART, of an estimated 13.7 million who need it. A major challenge to achieving this goal is the shortage of health care workers in low-income and low-resource areas of the world. Sub-Saharan African countries have 68% of the world’s burden of illness from AIDS, yet have only 3% of health care workers worldwide. The shortage of health care providers is primarily caused by a national and international ‘brain drain,’ poor distribution of health care workers within countries, and health care worker burnout.